Offsetting anthropogenic carbon emissions from biomass waste and mineralised carbon dioxide - Tripathi, Nimisha (Sci Rep, 2020)
The present work investigates biomass wastes and their ashes for re-use in combination with mineralised CO(2) in cement-bound construction products. A range of biomass residues (e.g., wood-derived, nut shells, fibres, and fruit peels) sourced in India, Africa and the UK were ashed and exposed to CO(2) gas. These CO(2)-reactive ashes could mineralise CO(2) gas and be used to cement ‘raw’ biomass in solid carbonated monolithic composites. The CO(2) sequestered in ashes (125–414 g CO(2)/kg) and that emitted after incineration (400–500 g CO(2)/kg) was within the same range (w/w). The CO(2)-reactive ashes embodied significant amounts of CO(2) (147–424 g equivalent CO(2)/kg ash). Selected ashes were combined with raw biomass and Portland Cement, CEM 1 and exposed to CO(2). The use of CEM 1 in the carbonated products was offset by the CO(2) mineralised (i.e. samples were ‘carbon negative’, even when 10% w/w CEM 1 was used); furthermore, biomass ashes were a suitable substitute for CEM 1 up to 50% w/w. The approach is conceptually simple, scalable, and can be applicable to a wide range of biomass ashes in a closed ‘emission-capture’ process ‘loop’. An extrapolation of potential for CO(2) offset in Europe provides an estimate of CO(2) sequestration potential to 2030.